REACTIONS TO MARTA MACHADO - Prado, Mariana Mota; Trebilcock, Michael (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
In a very insightful piece, Marta Machado calls attention to important failures in UPPs, one of the case studies in our book. She uses these failures to point to the fact that there were a series of informal rules and norms governing police behaviour in the State of Rio de Janeiro that were not effectively changed with the creation of UPPs. Moreover, she points to the complex interaction between these informal rules and norms and other institutions, such as the public prosecutor’s office and the judiciary, which are known for being important pieces in the puzzle of impunity for police abuse in Brazil. Our response acknowledges that UPPs may not have succeeded, but at the same time we emphasize that this particular failure is not a reason to assume that formal institutional reforms cannot promote significant change outside critical junctures.